2013
DOI: 10.1016/j.ccr.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-β-Dependent Activation of NF-κB in Stromal Cells Is Indispensable for the Survival of Chronic Lymphocytic Leukemia B Cells In Vivo

Abstract: SummaryTumor cell survival critically depends on heterotypic communication with benign cells in the microenvironment. Here, we describe a survival signaling pathway activated in stromal cells by contact to B cells from patients with chronic lymphocytic leukemia (CLL). The expression of protein kinase C (PKC)-βII and the subsequent activation of NF-κB in bone marrow stromal cells are prerequisites to support the survival of malignant B cells. PKC-β knockout mice are insusceptible to CLL transplantations, unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(156 citation statements)
references
References 53 publications
7
149
0
Order By: Relevance
“…The latter was defined by the formation of stress fibers and a-smooth muscle actin (a-SMA) accumulation ( Figure 6C), a characteristic of activated stroma and CAFs. 22,36 A similar formation of stress fibers was observed in stromal cells and fibroblasts, together with an increased expression of RhoA, a GTP-binding protein necessary for this actin skeleton remodeling (supplemental Figure 6A-C) when cells were incubated with exosomes. Exosomes produced by healthy donor B cells did not induce a-SMA expression ( Figure 6C).…”
Section: Cll Exosomes Induce Proliferation and Migration Of Stromal Cmentioning
confidence: 67%
See 2 more Smart Citations
“…The latter was defined by the formation of stress fibers and a-smooth muscle actin (a-SMA) accumulation ( Figure 6C), a characteristic of activated stroma and CAFs. 22,36 A similar formation of stress fibers was observed in stromal cells and fibroblasts, together with an increased expression of RhoA, a GTP-binding protein necessary for this actin skeleton remodeling (supplemental Figure 6A-C) when cells were incubated with exosomes. Exosomes produced by healthy donor B cells did not induce a-SMA expression ( Figure 6C).…”
Section: Cll Exosomes Induce Proliferation and Migration Of Stromal Cmentioning
confidence: 67%
“…Because CAF-mediated functions are strictly dependent on NF-kB signaling, we evaluated our transcriptome data set for changes in genes associated with CAF phenotype and performed unsupervised hierarchical clustering. A previously described, CAF gene expression signature 22,35 was observed in BM-MSCs treated with CLL exosomes ( Figure 5B). Unsupervised clustering also identified expression changes in gene signatures related to cell growth, survival, movement, and inflammation in BM-MSCs (supplemental Figure 4A).…”
Section: Cll Exosomes Induce An Inflammatory Phenotype In Stromal Cellsmentioning
confidence: 98%
See 1 more Smart Citation
“…50 Targeting PKC, and in particular PKCb, is especially pertinent given the recent findings of Lutzny et al, who demonstrated that PKCbII expression in bone marrow stromal cells is essential for the survival and development of CLL cells. 51 Therefore, inhibition of PKCb may modify the tumor microenvironment, which has been established to play a critical role in supporting CLL survival, proliferation and chemoresistance. 52 Collectively, our results demonstrate the potential for therapeutic agents targeting PI3K/PKCb−related signaling pathways, and highlight the translational applicability of the PKCa-KR mouse model as a pre-clinical model for the development of poor prognostic CLL.…”
Section: Discussionmentioning
confidence: 99%
“…This data set complements studies on proteins and microRNA transferred by CLL-vesicles 5-7 and might finally contribute to a detailed understanding of tumor-related aberrant gene expression in stromal cells, known to be crucial for CLL survival. 15 Interestingly, the disease-related mRNA signature was pronounced upon TLR engagement used as a milieu-mimic. Moreover, the transfer of enriched mRNA to monocytes and fibroblasts was demonstrated and the otherwise strictly lymphocyte-restricted protein expression of TCL1A was detectable in fibroblasts upon vesicle uptake.…”
mentioning
confidence: 99%